2015
DOI: 10.1016/j.ssc.2015.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Tc in BiS2-based superconductors NdO0.7F0.3BiS2 by substitution of Pb for Bi

Abstract: We succeed in enhancement of a superconducting transition temperature (T c ) for NdO 0.7 F 0.3 BiS 2 single crystal by partial substitution of Pb for Bi. The T c increases with increasing Pb concentration until 6%. The maximum T c zero is 5.6 K, which is the highest value among BiS 2 based superconductors synthesized under an ambient pressure. Pb substitution forBi induces lattice shrinkage along the c axis. These results reflect that superconductivity in this system is responsive to the lattice strain.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…This is because the Sb ion was substituted for the Bi ion located in the conduction layers. This increase in resistivity at RT has also been observed in Pb-substituted Ln(O,F)BiS2 (Ln = La, Nd) [15,20], on the other hand Pb substitution induced an enhancement of Tc. Therefore, the effect of substitution on superconductivity does not correlate to the strength of the scattering by the substituted atoms.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…This is because the Sb ion was substituted for the Bi ion located in the conduction layers. This increase in resistivity at RT has also been observed in Pb-substituted Ln(O,F)BiS2 (Ln = La, Nd) [15,20], on the other hand Pb substitution induced an enhancement of Tc. Therefore, the effect of substitution on superconductivity does not correlate to the strength of the scattering by the substituted atoms.…”
Section: Resultssupporting
confidence: 64%
“…Although a superconducting transition temperature (T c ) of Ln(O,F)BiS 2 is around 4 K, T c is increased when a lattice strain is introduced. One of the ways to introduce the lattice strain is by partial element substitution with a different ionic radius into Ln, Bi, or S site [10][11][12][13][14][15][16]. The strain introduced by partial element substitution in these crystals is the chemical pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Using single crystals, scanning tunneling microscopy/spectroscopy (STM/STS) has been performed to analyze the surface structure and the electronic states of BiS 2 -based compounds [58,75,158,200]. Machida et al observed checkerboardstripe electronic states for NdO 0.7 F 0.3 BiS 2 [75].…”
Section: Spectroscopymentioning
confidence: 99%
“…However, SbS 2 -based compounds do not show superconductivity [16]. On the other hand, the partial substitution of Ag [17], Cu [18], and Pb [19] for Bi-site all show superconductivity. Especially, Pb substitution enhances the superconducting transition temperature (T c ) [19].…”
Section: Introductionmentioning
confidence: 95%
“…On the other hand, the partial substitution of Ag [17], Cu [18], and Pb [19] for Bi-site all show superconductivity. Especially, Pb substitution enhances the superconducting transition temperature (T c ) [19]. These results indicate that substitution of the other elements for Bi-site may enhance superconducting properties.…”
Section: Introductionmentioning
confidence: 99%